INNOVATIONS IN PEDAGOGICAL ACTIVITY OF HIGHER SCHOOLS - Ponyaeva, (Revista Inclusiones, 2020)
The article deals with the actual current task of pedagogical activity - innovations in educational process. The article represents reviews of the research and works on the subject by other authors and definitions of the main concepts concerning the subject, and points out the main reasons stimulating professors and teachers of the higher schools to innovations. Having analyzed the scientific works on the subject, the author indicated innovative features of higher school pedagogics. The author represents the results of the research on readiness of the staff of Moscow Aviation Institute (National Research University) to introduce innovations in practice. Factors influencing the process of innovation such as: major advantages of innovative pedagogics from the point of view of pedagogical staff of higher schools, readiness of the teachers to master innovations, barriers to master innovations, awareness of the managers to accept innovations, branchers of literature devoted to innovative pedagogical technologies and their realization were also studied.